2016
DOI: 10.1016/j.neuropsychologia.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Differential association of left and right hippocampal volumes with verbal episodic and spatial memory in older adults

Abstract: The hippocampus plays a critical role in verbal and spatial memory, thus any pathological damage to this formation may lead to cognitive impairment. It is suggested that right and left hippocampi are affected differentially in healthy or pathologic aging. The purpose of this study was to test the hypothesis that verbal episodic memory performance is associated with left hippocampal volume (HV) while spatial memory is associated with right HV. 115 non-demented adults over age 70 were drawn from the Einstein Agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
95
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 43 publications
15
95
0
1
Order By: Relevance
“…Prior volumetric and functional neuroimaging studies revealed that the hippocampus was structurally and functionally asymmetric, suggesting that the left and right hippocampi are involved in qualitatively different aspects of memory formation. The right hippocampus is thought to be involved in processing of spatial memory, and the left hippocampus in the processing of verbal memory . Our current study supports the idea that the right hippocampus is involved in visuospatial memory.…”
Section: Discussionsupporting
confidence: 88%
“…Prior volumetric and functional neuroimaging studies revealed that the hippocampus was structurally and functionally asymmetric, suggesting that the left and right hippocampi are involved in qualitatively different aspects of memory formation. The right hippocampus is thought to be involved in processing of spatial memory, and the left hippocampus in the processing of verbal memory . Our current study supports the idea that the right hippocampus is involved in visuospatial memory.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, involvement of the hippocampus is a hallmark feature of AD and is considered to underlie the predominant amnesic syndrome [49]. Furthermore, previous studies reported correlation between scores of FCSRT free recall and atrophy in the left hippocampus and parahippocampus in AD and MCI subjects [19,20,22]. This finding is concordant with a recent study reporting that either the Rey Complex Figure delayed recall and the FCSRT delayed Recall, visual and a verbal episodic memory tests, are associated with total hippocampal volume in cognitively normal older adults [47].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, structural neuroimaging studies with the FCSRT Word version have exhibited an association between free recall and hippocampal volume measured with MRI-based volumetry in AD and MCI patients [18][19][20]. Free recall of the Picture version has been associated with left and right hippocampal volume, although the association was either stronger for left hippocampal, or only reported for the left hippocampal volume in AD patients and non-demented elderly people [21,22]. Recall of the spatial localization of items has been associated with bilateral hippocampal volumes, although somewhat stronger with the right hippocampal volume in AD patients [21].…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistent findings may be associated with methodological differences between studies, such as variations in test formats, volumetric procedures, and analytical strategies (Kaup et al, 2011; Ezzati et al, 2016). For example, in the present study, we used a cued-recall paired-associative learning task, which was more likely to recruit the hippocampus than an associative recognition task used in Becker et al (2015), to measure older individuals’ associative memory performance (Caplan and Madan, 2016).…”
Section: Discussionmentioning
confidence: 99%